Implementasi Metode PJBL dalam Meningkatkan Kualitas Pembelajaran Seni Musik di SMAN 1 Kayen - Hassya, Afif Alaudin; Edi Nugroho, Antonius (Universitas Sultan Ageng Tirtayasa, 2025)
The transition to an urban lifestyle has led to a transformation of meaning towards traditional objects such as sarongs. Illustrations are used by the Sobat Gurun Brand as a strategic visual representation in building a new meaning for sarongs as part of young people's self-expression in contemporary situations. This study aims to analyze the use of illustrations as a visual representation medium that reconstructs cultural meaning through Roland Barthes' semiotic approach and Stuart Hall's theoretical representation. Using a qualitative descriptive method, data was collected through visual observation of Sobat Gurun sarong products through its official website. The results show that the illustrations used are not limited to decorative ornaments, but function as a medium for constructing visual meaning. Cartoon characters, humorous expressions, and popular visual narratives become cultural signs that shift the meaning of sarongs from religious symbols to symbols of urban lifestyle and the identity of the younger generation. This visual strategy is considered effective in re-representing local culture to make it relevant to modern society.